The Relationship of Clinicopathological Parameters and Formula for Predicting Malondialdehyde Level in Feline Immunodeficiency Virus (FIV) - infected Cats - Sakundech, Kanissarinn; Aengwanich, Worapol (Journal of the Hellenic Veterinary Medical Society, 2022)
The objective of this study was to investigate clinicopathological parameters, malondialdehyde and total antioxidant power for analyzing correlation and predicting malondialdehyde in plasma of feline immunodeficiency virus (FIV)-infected cats. Body condition score (BCS), mucous membrane color score (MMCS), vital signs, hematological parameters, malondialdehyde and ferric reducing antioxidant power (FRAP) of 20 FIV-infected cats were examined. The correlation and multiple regression model were then analyzed. The results revealed the following. The correlation between hemoglobin vs. packed cell volume (PCV), total red blood cell (TRBC) vs. PCV, TRBC vs. hemoglobin, mean corpuscular hemoglobin (MCH) vs. mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC) vs. MCH, body temperature vs. eosinophil, total white blood cell (TWBC) vs. eosinophil, MMCS vs. platelet, eosinophil vs. malondialdehyde, PCV vs. FRAP, hemoglobin vs. FRAP, TRBC vs. FRAP and TRBC vs. FRAP were significantly positive correlated between pairs of these parameters (P<0.05), while body temperature vs. MCV, TRBC vs. MCV, heart rate vs. platelet, heart rate vs. platelet were significantly negatively correlated between pairs of parameters (P<0.05). A formula for predicting malondialdehyde was Heart Rate (beats/minute) = 166.341 + 5.438*Hemoglobin (g/dl) + 0.0009*Total White Blood Cell (cell/ml) - 1152.48*Malondialdehyde (µmol/ml) (MSE=132.2540; r2=0.85). These results indicated that there were correlations between some clinicopathological parameters, malondialdehyde and total antioxidant power and a formula for predicting malondialdehyde levels in plasma of FIV-infected cat was obtained.